2019
DOI: 10.21315/aamj2019.24.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and the Effectiveness of Monetary Policy: New Evidence from Malaysia

Abstract: This paper examines the relationship between financial development (FD) and the monetary policy effectiveness (MPE) in Malaysia. Two indicators designate the level of FD, namely liquid liabilities and stock market capitalisation, and gross fixed capital formation are used in estimating the determinants of MPE which is generated using structural vector auto regressive (SVAR) in an open economy approach. Accordingly, an autoregressive distributed lag (ARDL) model is used in examining the effects of FD and gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, findings also demonstrated that financial market development reduced the impact of monetary policy in Thailand via bank lending channel. Basa et al (2019) concluded that a co-integration existed between financial development and gross capital formation on MP effectiveness in Malaysia over 1991–2016. The empirical result also revealed that financial development significantly worsened the MP effectiveness on inflation and output, indicating that the efficacy of MP has been limited by a more advanced financial system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, findings also demonstrated that financial market development reduced the impact of monetary policy in Thailand via bank lending channel. Basa et al (2019) concluded that a co-integration existed between financial development and gross capital formation on MP effectiveness in Malaysia over 1991–2016. The empirical result also revealed that financial development significantly worsened the MP effectiveness on inflation and output, indicating that the efficacy of MP has been limited by a more advanced financial system.…”
Section: Literature Reviewmentioning
confidence: 99%